2019
DOI: 10.1016/j.preghy.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth with remote blood pressure monitoring for postpartum hypertension: A prospective single-cohort feasibility study

Abstract: Objective: Investigate feasibility of telehealth with remote blood pressure monitoring for management of hypertension in postpartum women at risk of severe hypertension after hospital discharge. Methods: In a single-center, prospective single-cohort feasibility study, women with hypertension in pregnancy participated in a postpartum telehealth intervention for blood pressure management after discharge. The primary feasibility outcome measures were recruitment and retention through 6 weeks postpartum. Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 25 publications
2
79
0
Order By: Relevance
“…Other forms of distance care, e.g. evidence-based mobile health apps or other remote monitoring [26,27], may also offer a more accessible way to delivery ongoing postpartum care, particularly for elements of care that do not require facetime with a provider, e.g. education about resuming sexual activities or diet and weight trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of distance care, e.g. evidence-based mobile health apps or other remote monitoring [26,27], may also offer a more accessible way to delivery ongoing postpartum care, particularly for elements of care that do not require facetime with a provider, e.g. education about resuming sexual activities or diet and weight trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 It has also been observed that home blood pressure monitoring in cases with hypertension in pregnancy was acceptable to most patients and could detect elevation in blood pressure. 19,20 Home monitoring, in addition allows for active participation of patients in their self-care and promotes self-efficacy especially during hard times of COVID-19 pandemic .…”
Section: Telemedicine For Antenatal Carementioning
confidence: 99%
“…Specifically, most women reported that they found the technologies easy to use, would recommend them to other women, and preferred this model of hypertension management to in-person clinic visits. [8][9][10] One study found remote postpartum blood pressure monitoring increased in-person care engagement, with 88% of women who used remote monitoring attending their in-person 6-week postpartum visit, compared with a baseline attendance rate of 66%. 10 Furthermore, 82% of patients expressed relief in knowing that a nurse was monitoring their blood pressure on a daily basis.…”
Section: Current Evidence For Postpartum Remote Blood Pressure Monitomentioning
confidence: 99%
“…Similarly, the majority of studies on remote blood pressure monitoring were conducted in English-speaking populations, and phone-accessible translation services and multilanguage text messaging options will be critical to establishing more robust evidence for deploying remote monitoring universally and equitably. [8][9][10][11] The impact of changes in insurance coverage for telehealth and blood pressure cuffs during COVID-19 is also a critical area for research. Prior to the pandemic, limited insurance coverage during the postpartum period, as well as for telehealth visits, presented a major barrier to scaling up remote hypertension monitoring.…”
Section: Future Research Directions For Postpartum Remote Monitoringmentioning
confidence: 99%
See 1 more Smart Citation